(untitled)
The purpose of this study is to determine the effect of work discipline and work motivation on employee productivity. This research was conducted at PT. Arta Boga Brilliant Denpasar Branch. The population of this study were all employees of PT. Arta Boga Cemerlang Denpasar Branch totaled 37 people. The sampling technique used a saturated sample, namely using the entire population as a sample, as many as 37 people. The research methods used in this study and instrument tests, classical assumption test, multiple linear regression, coefficient of determination, t test and F test. The results showed that, work discipline had a positive and significant effect on work productivity of employees of PT. Arta Boga Cemerlang Denpasar Branch of 0.002